COVID-19 impact on dispute resolution – the utilization of mediation in the settlement of construction disputes in Malaysia - Zulhabri Ismail,; Nurul Safiyah Othman, (Penerbit Universiti Kebangsaan Malaysia, 2023)
COVID-19 outbreak on mediation, to analyse the causes of mediation for not being fully utilised, and to appraise the approach to increase the usage of mediation as a dispute resolution method during COVID-19 outbreak in Malaysia. Qualitative data were collected through semi-structured interviews. Findings indicated that COVID-19 has replaced face-to-face mediation procedures with online mediation. In addition, many approaches to increasing the use of mediation as a means of settling construction disputes have been identified, the most significant of which would be the enforcement of mediation settlement by the Malaysian government. Future research should focus on the input from mediators, contractors, and all construction players to improve the usage of mediation as a settlement of construction disputes in Malaysia.